Kant on the Dignity of Autonomy and Respect for the Moral Law - Fasoro, Adeniyi Sunday (Studia Kantiana, 2023)
I explore two claims that are often attributed to Kant: first, that conformity with the moral law without freedom lacks intrinsic value in itself, and second, that the moral law is a mere means to preserve and promote our freedom. In this paper, I investigate whether freedom can be intrinsically valuable without adherence to the moral law. I begin with the examination of what it means for freedom to be thought of as "an inner value" and "an end in itself". I suggest that when Kant uses an expression such as "by means of the moral law", he does not mean that the moral law only serves the purpose of preserving and promoting freedom without its own intrinsic value. Indeed, I provide textual evidence that the moral law precedes freedom and must be respected unconditionally because it is a sufficient incentive that is good in itself. I argue that respect for the law is required in order for freedom to be lawful and without it, it would be lawless.